"Spongy, slimy, cosy & more" - Commemorative Volume in Celebration of the 60th Birthday of Joachim Reitner - Wiese, Frank (Universitätsverlag Göttingen, 2014)
This volume contains papers presented in part at a symposium held in May 2012 at Göttingen University, to honour Professor Joachim Reitner for his numerous contributions to the fields of geobiology, geology, and palaeontology. Our present volume reflects the breadth of Reitner's interests and accomplishement with tributes and research or review papers by his students, former students, collaborators, and friends. The symposium was held in conjunction with Joachim Reitner's 60th birthday.